Earth architecture : ancient and new methods for durability improvement - Eires, R. (2013)
Quite a big part of the country and world’s heritage was made using unfired earth constructions. The new earth buildings, as well as the conservation of the existent heritage, need scientific knowledge to allow higher durability. This durability is particularly conditioned by erosion caused by water action, especially in countries with high rainfall index. Analyzing the old building techniques, that allow protection on the earth material from water action, it is possible to understand how many earth buildings were preserved, during several centuries, resisting to harsh weather conditions. Among these techniques there are specially the incorporation of biopolymers (such as oils or fats), the addition of some minerals and stabilization with lime. However, this knowledge seems to have been forgotten. The authors study new methods of soil stabilization, with lime and biopolymers, adapting the ancient knowledge to improve the durability, specially related to the water action.